Chasing the dream: Emerging musicians' migration to London during the cost-of-living crisis - Kelman, Kristina (Journal of International Students, 2025)
While research abounds on musicians’ precarity, emerging student musicians remain understudied, especially amidst migration for opportunity. This timely study addresses critical gaps by qualitatively exploring the experiences of popular music students who migrate to London for education and prospective careers. Set during the UK’s recent cost-of-living crisis (2021-2022), rich interview data provides empirical insights into an important yet often overlooked group during a pivotal life transition. Findings reveal intensified financial and work-life struggles; however, remarkable resilience also emerges alongside identity shifts and peer bonds. Most significantly, despite hardships, London’s enduring promise leads most to stay for perceived, unparalleled creative opportunities. Practical recommendations provide an important starting point for strengthening creative training and better-nurturing talents during an unsettled era.